1997
DOI: 10.1071/mf97203
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of environmental factors and processing techniques on Panulirus cygnus morbidity and mortality during simulated live shipments

Abstract: In this study, conducted in collaboration with the Western Australian rock lobster industry during the 1992–93 fishing season, daily records were made on morbidity and mortality of western rock lobsters, Panulirus cygnus, held in commercial shipping (export) cartons. The aims were to measure the rates of morbidity + mortality and to identify patterns of correlation of morbidity + mortality rates for a range of environmental variables recorded by the processors. In three processing units, the rate of morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Samet et al (1996) reported that precooling has an anaesthetic effect and prolongs survival of prawns during transport. Spanoghe and Bourne (1997) also reported increased survival at transport temperatures ranging from 12 to 15°C. Low temperatures (below 12°C) were shown to lower or delay mortality in animals infected with White spot syndrome virus even though no significant differences were observed in THC or counts of granular cells (Jiravanichpaisal et al, 2004).…”
Section: Temperature Fluctuationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Samet et al (1996) reported that precooling has an anaesthetic effect and prolongs survival of prawns during transport. Spanoghe and Bourne (1997) also reported increased survival at transport temperatures ranging from 12 to 15°C. Low temperatures (below 12°C) were shown to lower or delay mortality in animals infected with White spot syndrome virus even though no significant differences were observed in THC or counts of granular cells (Jiravanichpaisal et al, 2004).…”
Section: Temperature Fluctuationsmentioning
confidence: 87%
“…Several studies have reported a retarding effect of temperature on physiology (Wachter and McMahon, 1996), immunity (Truscott and White 1990;Cheng and Chen, 2000;McGaw, 2003;Cheng et al, 2005) and survival (Samet et al, 1996;Spanoghe and Bourne, 1997;Huang and Chen, 2001). Samet et al (1996) reported that precooling has an anaesthetic effect and prolongs survival of prawns during transport.…”
Section: Temperature Fluctuationsmentioning
confidence: 97%
“…The sampled lobsters were visually assessed for vigour (Spanoghe & Bourne 1997) size, sex, and damage. A pleopod tip was taken from each for moult staging.…”
Section: Application Of Stressmentioning
confidence: 99%
“…Crustaceans rapidly accumulate lactate and ammonium in their hemolymph with air exposure, and the effects tend to be exacerbated by increases in temperature (Vermeer, 1987;Woll et al, 2010). Numerous physiological studies have been aimed at understanding the physiological consequences of emersion because of relevance to live shipment for rock lobsters (Spanoghe and Bourne, 1997;Paterson et al, 2005), clawed lobsters (Ridgway et al, 2006;Lorenzon et al, 2007), and edible crab (Barrento et al, 2009). Acidosis is a common effect of emersion that can have lasting effects on various tissues.…”
Section: Discussionmentioning
confidence: 98%
“…"Tail flip" has been used to characterize condition in rock lobsters (Panulirus argus and P. cygnus) (Vermeer, 1987;DiNardo et al, 2002), and professional graders in Australia routinely evaluate the condition of P. cygnus on the basis of behavioral characteristics to predict survival for the live market trade (Paterson et al, 2005). Spanoghe and Bourne (1997) used a combination of tail flip response, and movements of the appendages and eye stalks to classify the condition of P. cygnus as "dead", "moribund", "weak", "healthy", or "very healthy", and Harris and Ulmestrand (2004) used a similar system of observations to evaluate the condition of Norwegian lobsters (Nephrops norvegicus). Others have incorporated behavior-based vitality indices to evaluate handling stress in lobsters (Brown and Caputi, 1983;Castro et al, 2003) and crabs (Stevens, 1990;Tallack, 2007).…”
Section: Discussionmentioning
confidence: 99%